The Effectiveness of Phase III Cardiac Telerehabilitation on Functional Capacity, Adherence, Rehospitalization, and Quality of Life: A Systematic Review and Meta-Analysis - Wini Widia Maulanie; Cecep Eli Kosasih; Hikmat Rudyana (Jurnal Ners, 2026)
Cardiovascular disease remains the leading cause of global morbidity and mortality. Phase III cardiac rehabilitation plays a crucial role in long-term maintenance and secondary prevention; however, patient adherence and program sustainability remain suboptimal due to limited access, geographical barriers, and resource constraints. Phase III cardiac telerehabilitation has been developed as a digital-based alternative to support patient engagement and continuity of rehabilitation. This study aimed to analyze the effectiveness of phase III cardiac telerehabilitation on functional capacity, adherence, rehospitalization, and quality of life compared with conventional cardiac rehabilitation or standard care. This study was a systematic review and meta-analysis of 15 randomized controlled trials published between 2015 and 2025. The study population included adult patients with cardiovascular disease who had completed phase II cardiac rehabilitation and participated in phase III cardiac telerehabilitation programs. Outcomes assessed included functional capacity (VO₂peak, Six-Minute Walk Test, and metabolic equivalents), program adherence, rehospitalization, and quality of life. Data were analyzed using Review Manager (RevMan) version 5.3 with fixed-effect or random-effect models according to heterogeneity levels. The meta-analysis demonstrated that phase III cardiac telerehabilitation significantly improved functional capacity measured by VO₂peak with low heterogeneity (I² = 0%), as well as quality of life (SMD = 0.16; 95% CI 0.04–0.28; p = 0.01) and patient adherence to rehabilitation programs. However, no significant differences were observed in the Six-Minute Walk Test, metabolic equivalents, or rehospitalization compared with control groups. Based on these findings, phase III cardiac telerehabilitation is recommended as an effective and safe strategy to support the long-term sustainability of cardiac rehabilitation and improve patients’ quality of life.